The international phase 4 validation study of the EORTC QLQ‐SWB32: A stand‐alone measure of spiritual well‐being for people receiving palliative care for cancer. (4th August 2017) - Vivat, B.; Young, T.E.; Winstanley, J.; Arraras, J.I.; Black, K.; Boyle, F.; Bredart, A.; Costantini, A.; Guo, J.; Irarrazaval, M.E.; Kobayashi, K.; Kruizinga, R.; et al.
Abstract : The EORTC Quality of Life Group has just completed the final phase (field‐testing and validation) of an international project to develop a stand‐alone measure of spiritual well‐being (SWB) for palliative cancer patients. Participants ( n  = 451)—from 14 countries on four continents; 54% female; 188 Christian; 50 Muslim; 156 with no religion—completed a provisional 36‐item measure of SWB plus the EORTC QLQ‐C15‐PAL (PAL), then took part in a structured debriefing interview. All items showed good score distribution across response categories. We assessed scale structure using principal component analysis and Rasch analysis, and explored construct validity, and convergent/divergent validity with the PAL. Twenty‐two items in four scoring scales (Relationship with Self, Relationships with Others, Relationship with Someone or Something Greater, and Existential) explained 53% of the variance. The measure also includes a global SWB item and nine other items. Scores on the PAL global quality‐of‐life item and Emotional Functioning scale weakly‐moderately correlated with scores on the global SWB item and two of the four SWB scales. This new validated 32‐item SWB measure addresses a distinct aspect of quality‐of‐life, and is now available for use in research and clinical practice, with a role as both a measurement and an intervention tool.